INTEGRATING DIGITAL ASSESSMENT IN ISLAMIC EDUCATION WITHIN THE MERDEKA CURRICULUM : A STUDY CASE AT SMP NEGERI 2 NGEMPLAK - Linda Asmara; Ari Anshori; Muhammad Wildan Shohib (Proceeding of International Conference of Islamic Education, 2025)
This study aims to analyze the implementation of digital-based assessment in Islamic Religious Education (PAI) within the framework of the Merdeka Curriculum at SMP Negeri 2 Ngemplak. Using a descriptive qualitative approach, data were collected through classroom observations, in-depth interviews with PAI teachers, and supporting documentation. The research explores how digital tools are integrated into the assessment process and how these methods align with the principles of the Merdeka Curriculum, which emphasizes holistic, student-centered learning and character development. The findings reveal that PAI teachers at SMP Negeri 2 Ngemplak have adopted a comprehensive assessment strategy that addresses cognitive, affective, and psychomotor domains. The evaluation process follows systematic stages: planning, implementation, data processing, interpretation, and reporting. Digital tools, particularly Google Forms and Quizizz, are utilized as primary instruments for formative and summative assessments. These tools enable efficient question delivery, automatic grading, real-time feedback, and secure data storage, enhancing the overall evaluation process. However, the integration of digital assessment is not without challenges. Issues such as limited access to devices, unstable internet connectivity, and the need for increased digital literacy among students and teachers have been identified as significant barriers. Despite these obstacles, the study demonstrates a progressive shift toward digital transformation in educational assessment, even within Islamic education subjects. This research contributes to the growing body of literature on the application of educational technology in religious instruction and provides practical insights for educators and policymakers aiming to enhance assessment practices in line with the goals of the Merdeka Curriculum. The findings suggest that with adequate support and infrastructure, digital assessment can serve as an effective tool for evaluating diverse student competencies in Islamic Education.